Low-cost microarray thin-film electrodes with ionic liquid gel-polymer electrolytes for miniaturised oxygen sensing - Lee, J.; Silvester, Debbie (Royal Society of Chemistry, 2016)
A robust, miniaturised electrochemical gas sensor for oxygen (O2) has been constructed using a commercially available Pt microarray thin-film electrode (MATFE) with a gellified electrolyte containing the room temperature ionic liquid (RTIL) 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([C2mim][NTf2]) and poly(methyl methacrylate) (PMMA) in a 50:50 mass ratio. Diffusion coefficients and solubilities for oxygen in mixtures of PMMA/RTIL at different PMMA doping concentrations (0-50% mass) were derived from potential step chronoamperometry (PSCA) on a Pt microdisk electrode. The MATFE was then used with both the neat RTIL and 50% (by mass) PMMA/RTIL gel, to study the analytical behavior over a wide concentration range (0.1 to 100 vol% O2). Cyclic voltammetry (CV) and long-term chronoamperometry (LTCA) techniques were employed and it was determined that the gentler CV technique is better at higher O2 concentrations (above 60 vol%), but LTCA is more reliable and accurate at lower concentrations (especially below 0.5% O2). In particular, there was much less potential shifting (from the unstable Pt quasi-reference electrode) evident in the 50% PMMA/RTIL gel than in the neat RTIL, making this a much more suitable electrolyte for long-term continuous oxygen monitoring. The mass production and low-cost of the electrode array, along with the minimal amounts of RTIL/PMMA required, make this a viable sensing device for oxygen detection on a bulk scale in a wide range of environmental conditions.